Corporate Governance in the Aftermath of the Global Financial Crisis, Volume IV : Emerging Issues in Corporate Governance. - Rezaee, Zabihollah (Business Expert Press, 2018)
Corporate governance has made impressive progress in the past two decades in the aftermath of financial scandals at the turn of the twenty-first century and the 2007-2009 global financial crisis. Corporate governance has moved to the center stage of corporate culture and business model in defining the roles and responsibilities of all corporate gatekeepers and holding them accountable for contributing to shared value creation for all stakeholders. Today, corporate governance functions in an environment of ever-increasing regulatory reforms established to protect investors and the public from financial scandals and crisis and restore public trust and investor confidence in public financial information and financial markets. Corporate governance, in complying with the ever-increasing regulatory reforms, is striving to improve effectiveness. This volume presents emerging issues in corporate governance in the areas of board oversight function, managerial operation and performance, and gatekeepers' responsibilities and accountabilities. Recent regulatory reforms have created a better power-sharing balance between shareholders, the board of directors, and management in contributing to shared value creation for all stakeholders. This volume consists of five chapters addressing emerging issues in corporate governance including the global perspectives, convergence in corporate governance, and emerging issues relevant to shareholders, directors, and executives. This volume also examines the corporate governance of private and not-for-profit organizations and the future of corporate governance. Anyone who is involved with corporate governance, the financial reporting process, internal and external audit functions, and compliance with laws, rules and regulations should be interested in this volume. Specifically, corporations and their boards of directors and audit committees, executives, internal and external auditors, accountants, governing bodies, policy makers, regulators, users of financial statements (investors, creditors, pensioners), and other professionals (attorneys, financial analysts, bankers) and scholars conducting research in corporate governance will benefit from this volume.